1996
DOI: 10.1073/pnas.93.24.13808
|View full text |Cite
|
Sign up to set email alerts
|

Calexcitin: A signaling protein that binds calcium and GTP, inhibits potassium channels, and enhances membrane excitability

Abstract: A previously uncharacterized 22-kDa Ca 2؉ -binding protein that also binds guanosine nucleotides was characterized, cloned, and analyzed by electrophysiological techniques. The cloned protein, calexcitin, contains two EFhands and also has homology with GTP-binding proteins in the ADP ribosylation factor family. In addition to binding two molecules of Ca 2؉ , calexcitin bound GTP and possessed GTPase activity. Calexcitin is also a high affinity substrate for protein kinase C. Application of calexcitin to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 63 publications
5
51
1
1
Order By: Relevance
“…Electrophysiological studies showed that low concentrations of squid calexcitin had a strong inhibitory effect on human K + channels (Nelson et al, 1996). These findings suggest that a functionally related protein exists in mammals and may play a similar role in the regulation of potassium channels.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Electrophysiological studies showed that low concentrations of squid calexcitin had a strong inhibitory effect on human K + channels (Nelson et al, 1996). These findings suggest that a functionally related protein exists in mammals and may play a similar role in the regulation of potassium channels.…”
Section: Introductionmentioning
confidence: 68%
“…Cloning and sequencing of squid calexcitin cDNA showed that the protein consists of 191 amino acids and has sequence similarity with several sarcoplasmic calcium-binding proteins (SCPs) and some elements of sequence similarity with GTP-binding proteins of the ADPribosylation factor family (Nelson et al, 1996;Gombos et al, 2001). Squid calexcitin has significant sequence identity (28%) with an invertebrate SCP of known X-ray structure, referred to as ASCP (an SCP from the proto-vertebrate marine organism Amphioxus; Cook et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hermissenda, this activation causes PKC to translocate to the cell membrane (McPhie et al, 1993). Subsequently, this translocation induces secondary pathway cascades that lead to the activation and increased production of the GTP/Ca 2ϩ -binding protein calexcitin (Nelson et al, , 1996(Nelson et al, , 1999Ascoli et al, 1997;Kuzirian et al, 2001), the release of internal calcium from the endoplasmic reticulum, and the reduction of outward K ϩ currents that triggers a rise in the resting potential and the establishment of a long-lasting depolarization. Early gene activation is also associated with PKC up-regulation caused by these same associative conditioning regimes .…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that actin-related protein is associated with intermediate memory in Hermissenda (Crow and Xue-Bian 2002). Calexcitin, extracted from the conditioned Hermissenda type B photoreceptors, is a potent signaling protein that binds calcium and GTP, inhibits potassium channels due to phosphorylation by PKC, and enhances membrane excitability (Nelson et al 1996). Thus activation of the conditioning specific calcium sensor G-proteins, calexcitin, might contribute to contraction at the B cell terminal branches.…”
Section: ϫ4mentioning
confidence: 99%